Access and feasibility of orthopaedic training in the independent sector – A Deanery's experience. Issue 5 (October 2022) - Lenihan, Jonathan; Ngu, Albert Wee Tun; ,; Vince, Alastair; Kang, Sertaz-Niel; Sanghrajka, Anish; Tansey, Rosamund; Patel, Jaison; Liew, Ignatius; Rooney, Aaron; Matthews, William; Sadique, Hammad; et al.
Abstract: Introduction: Coronavirus (COVID-19) has negatively impacted healthcare around the world. It has had a major impact on orthopaedic training. The independent sector has been proposed as a facility for future training. Our aim was to provide an overview of the current higher surgical trainees' experience in the independent sector. Method: Training orthopaedic registrars within the East of England deanery were asked to complete an electronic questionnaire of their training experience in the independent sector between 5th November to 2nd December 2020. Results: 57 of 64 registrars (89%) from across all thirteen regional training hospitals responded. 44% attended the independent sector, but 7 only assisted (28%). No third year trainees went, but there was an even spread of other training years attending a mean of four sessions. Sixty-six indicative procedures were performed, all with supervisors scrubbed. Second year trainees performed the most cases with 4 on average. Completion of work based assessments was low. 20% trainees reported a negative experience. 80% enjoyed themselves. 52% felt they achieved their goals. 29% trainees felt that independent sector operating would compensate for the shortfall in training brought about by COVID-19. The main obstacles to independent sector training were lack of access and opportunity (51%) and poor induction and paperwork issues (22%) Conclusion: This is the first deanery-wide assessment of access to and training within the independent sector due to COVID-19. Independent sector operating for orthopaedic trainees is feasible on scale and should be embedded to supplement training in the future. In their current state independent sector facilities are not easily and universally accessible to fulfil training needs. Highlights: COVID 19 has impacted trauma & orthopaedics training within our region. Trainee's experience in the independent sector during the COVID 19 pandemic. Training in the independent sector can potentially be a viable alternative. '#NoTrainingTodayNoSurgeonsTomorrow'